Non‐native congeneric trees are poor‐quality host plants for a larval Lepidopteran - Desiree L. Narango; Katherine Straley (Ecosphere)
Abstract In managed ecosystems, cultivated plant diversity is a collection of native and introduced species composed of varying plant origins across scales: locally native, non‐locally native, and non‐native. Non‐local and non‐native plant species may be ill‐suited as host plants for locally native insects. Yet, we lack information on the population‐ and individual‐level consequences of introduced plants to phytophagous insects. Promethea moth (Callosamia promethea) is a Lepidopteran species regionally specialized to Prunus in the Northeastern United States. Here, we used a rearing experiment to compare Promethea caterpillar performance on 14 different Prunus host plants commonly found naturally and in horticulture and two non‐hosts. Across all measures, Prunus serotina supported the highest survival, fastest growth, and largest larval biomass. We found little difference between locally native and non‐local Prunus across most measures; however, few non‐native Prunus supported living larvae to the fifth instar, and surviving larvae had reduced growth and biomass. Our results indicate that non‐native congeners are poor replacements for locally native tree species in supporting specialized Lepidoptera. However, non‐local, regionally native species in cultivation may serve as adequate, albeit suboptimal, host plants. These results further our understanding of how selection for plant traits or species impacts biodiversity in novel and managed ecosystems.